Diagnosing earth's tipping points: where we stand in the Anthropocene - Rockström, Johan (Frontiers in Public Health, 2025)
Human and planetary health are inextricably linked through complex adaptive systems. This perspective, adapted from the 2024 Virchow Lecture, highlights how accelerating anthropogenic pressures are destabilizing the Earth system. Scientific evidence shows that six of nine planetary boundaries have already been transgressed, increasing the risk of irreversible tipping points. The Holocene epoch, a period of climate stability underpinning human civilization, serves as a benchmark for a “safe and just operating space” for humanity. Staying within this space is essential not only for ecological resilience but also for achieving the United Nations Sustainable Development Goals (SDGs), which depend on a stable Earth system. The biosphere's capacity to regulate climate is under severe threat. Without urgent action to restore and protect nature and its natural carbon sinks, even full decarbonization by 2050 may not prevent systemic breakdowns. The Earth still exhibits self-dampening feedbacks, which offer a narrow but critical opportunity to shift course. This article calls for integrated action across climate, health, and sustainability science and introduces the Planetary Health Check as an annual tool to assess Earth's condition. The path to a thriving future begins with recognizing planetary health as foundational to human wellbeing and justice.